LEGAL PROTECTION OF STREET CHILD ABANDONMENT VICTIMS WITHOUT PARENTAL CARE - Firmansyah Siregar (UNES Law Review, 2023)
Street children as one of the problems in the field of children that occur as a result of the inability of parents to raise children so that street children are vulnerable to discriminatory behavior in society. Street children need a protection and welfare of children which can be realized with institutional and regulatory support, children in a general sense get attention not only in science, but can be noticed from a centralistic point of view of life, such as religion, law and psychology which makes children increasingly national and in the actual social environment Street children must still be cared for and protected because after all street children have the same rights and position as the next generation of development and ideals of the nation, state and religion because these children will later maintain, maintain and develop the results of their predecessors a child basically need care, protection, teaching, and affection.